1997
DOI: 10.1046/j.1468-2982.1997.1705608.x
|View full text |Cite
|
Sign up to set email alerts
|

A CPH-Like Picture in Two Patients with an Orbitocavernous Sinus Syndrome

Abstract: Two patients with retroorbital pain syndromes with or without paresis of cranial nerves developed weeks after ipsilateral headache resembling chronic paroxysmal hemicrania (CPH) but without autonomic features. These findings might support the hypothesis that CPH may be caused by a pathological process in the region of the cavernous sinus, as has been proposed for the Tolosa-Hunt syndrome (THS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…42,43 Similarly, secondary chronic paroxysmal hemicrania has also been reported with a syndrome like Tolosa-Hunt syndrome. 44,45 In our group of 11 patients, indomethacin relieved pain in eight of them. One of these patients had to use amitriptyline and pizotifen concurrently to achieve complete pain relief.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…42,43 Similarly, secondary chronic paroxysmal hemicrania has also been reported with a syndrome like Tolosa-Hunt syndrome. 44,45 In our group of 11 patients, indomethacin relieved pain in eight of them. One of these patients had to use amitriptyline and pizotifen concurrently to achieve complete pain relief.…”
Section: Discussionmentioning
confidence: 67%
“…By analogy to cluster headache, calcium‐channel blockers such as nicardipine and flunarizine have been successful in aborting episodic paroxysmal hemicrania, 38 as has verapamil in chronic paroxysmal hemicrania, 39–41 with a similar efficacy to indomethacin. Chronic paroxysmal hemicrania can coexist with trigeminal neuralgia 44 just as cluster headache 42,43 . Similarly, secondary chronic paroxysmal hemicrania has also been reported with a syndrome like Tolosa–Hunt syndrome 44,45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cases reported by Foederreuther et al (9) showed many features that resemble the Tolosa–Hunt syndrome but later on, the symptoms of both cases were similar to CPH, including the response to indomethacin. Structural abnormalities in the cavernous sinus region were present in both cases.…”
Section: Discussionmentioning
confidence: 89%
“…In the past, the absence of radiographic evidence of inflammation in patients with THS was confusing to clinicians, and a diagnosis of “idiopathic painful ophthalmoplegia” was applied to these patients [30-32]. The eponym of “benign THS” was first introduced by La Mantia et al in 2006 to describe these patients [9].…”
Section: Discussionmentioning
confidence: 99%